Electron Transfer Reaction of Iron(III)-bipyridyl Complex with Diphenyl Sulfide - Balakumar, Pathakaraimuthu; Balakumar, Subramaniam; Subramaniam, Perumal (Asian Journal of Chemistry, 2010)
The oxidation of diphenyl sulfide in aqueous methanol at constant [H+] and ionic strength with iron(III)-bipyridyl complex has been investigated under pseudo first order condition by spectrophotometric technique. The reaction follows first order kinetics with respect to substrate and oxidant and proceeds through rate determining electron transfer (ET) from organic sulfide to iron(III). The rate constant values are observed for organic sulfide with oxidant Fe(bpy)3 3+. The product of oxidation is sulfoxide.